Pengaruh Harga dan Trust Terhadap Loyalitas Pengguna Layanan Ojek Online (Studi Kasus Pada Pengguna Gojek Indonesia) - Shofwaana, Reyza Ardelia; Yusuf, Abdul (Universitas Pahlawan Tuanku Tambusai, 2025)
The rapid transformation in the business landscape due to digitalization has brought about significant changes. One sector that is experiencing rapid change is the online transportation services industry such as Gojek in Indonesia, increasing competition between service providers. Factors such as price and trust play an important role in influencing customer loyalty. This research aims to determine the effect of price and trust on customer loyalty, with a focus on Gojek users in Indonesia. The research design uses quantitative methodology with a sample of 100 Gojek users using purposive sampling. Data collection includes primary data from user questionnaires and secondary data from the literature. The analysis uses multiple regression via Smart PLS 4 software. The research results show that there is a significant positive influence of price and trust on customer loyalty, with price having a higher influence.